Hypoxia-Inducible Factor Is Critical for Pathogenesis and Regulation of Immune Cell Functions in Rheumatoid Arthritis - Guo, Xin; Chen, Guangjie (Frontiers in Immunology, 2020)
Rheumatoid arthritis(RA) is a common autoimmune disease with characteristics of synovial inflammation, pannus formation, cartilage destruction, and bone erosion. Further, the inflammation is linked to increased oxygen consumption, resulting in hypoxia within the inflammatory area. Hypoxia-inducible factor (HIF) was reported to be associated with adaptation to the hypoxic microenvironment in the RA synovium. Here, we have briefly summarized the structure and expression of HIF. Moreover, the function of HIF in inflammation, angiogenesis, cartilage damage, and immune cells of RA has been discussed.